2003
DOI: 10.1124/jpet.102.043596
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nicotine Treatment Leads to Sustained Stimulation of Tyrosine Hydroxylase Gene Transcription Rate in Rat Adrenal Medulla

Abstract: Nicotine is a powerful stimulant of the sympathoadrenal system, causing the release of peripheral catecholamines and activation of catecholamine biosynthesis. In previous reports, we have studied the mechanisms by which short-term nicotine treatment regulates tyrosine hydroxylase (TH) in adrenal medulla. In this report, we study the effects of chronic nicotine treatment on adrenal TH gene expression. Rats were injected with either saline or nicotine twice per day for up to 14 days. Chronic nicotine treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…This phenomenon would explain lower TH expression as well as higher levels of catecholamines in association with lower levels of cholinergically stimulated release. In contrast, other studies have shown higher TH expression and activity in the adrenal medulla of rats exposed acutely (Tank et al 1998, Sterling & Tank 2001 or chronically to nicotine (Sun et al 2003). Cheng et al (2005) observed no changes in Th mRNA levels in rats that were chronically exposed.…”
Section: Changes In Suckling Pupsmentioning
confidence: 47%
“…This phenomenon would explain lower TH expression as well as higher levels of catecholamines in association with lower levels of cholinergically stimulated release. In contrast, other studies have shown higher TH expression and activity in the adrenal medulla of rats exposed acutely (Tank et al 1998, Sterling & Tank 2001 or chronically to nicotine (Sun et al 2003). Cheng et al (2005) observed no changes in Th mRNA levels in rats that were chronically exposed.…”
Section: Changes In Suckling Pupsmentioning
confidence: 47%
“…It has also been predicted that a characteristically rapid desensitization of the direct target nAChRs, following their initial activation by NC, may yield contradicting depression-related behavioral alterations [45]. Furthermore, the NC-induced depression-related behavioral alterations may occur in accordance with neuroendocrine alterations such as the levels of brain monoamines and stress hormones, in which the time course coincides at least partly with the neuroendocrine responses caused by the depression-inducing stressors, regardless of the behavioral outcome [46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying the appearance of these dual contrary behavioral -sympathoadrenal system, increased stress hormones, etc.) have been reported to accompany NC treatment, and seem to be affected by differing conditions such as the number of NC administrations (Kirch et al, 1987;Morse, 1989;Sun et al, 2003). Furthermore, the time course of those of these dual behavioral effects.…”
Section: Discussionmentioning
confidence: 99%